Effect of Hydrogen Peroxide on Cyanobacterial Biofilms - Maria João Romeu; João Morais; Vítor Vasconcelos; Filipe Mergulhão (MDPI AG, 2023)
Although a range of disinfecting formulations is commercially available, hydrogen peroxide is one of the safest chemical agents used for disinfection in aquatic environments. However, its effect on cyanobacterial biofilms is poorly investigated. In this work, biofilm formation by two filamentous cyanobacterial strains was evaluated over seven weeks on two surfaces commonly used in marine environments: glass and silicone-based paint (Sil-Ref) under controlled hydrodynamic conditions. After seven weeks, the biofilms were treated with a solution of hydrogen peroxide (H2O2) to assess if disinfection could affect long-term biofilm development. The cyanobacterial biofilms appeared to be tolerant to H2O2 treatment, and two weeks after treatment, the biofilms that developed on glass by one of the strains presented higher biomass amounts than the untreated biofilms. This result emphasizes the need to correctly evaluate the efficiency of disinfection in cyanobacterial biofilms, including assessing the possible consequences of inefficient disinfection on the regrowth of these biofilms.